2017
DOI: 10.3390/w9100786
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Nitrogen and COD from Reclaimed Water during Long-Term Simulated Soil Aquifer Treatment System under Different Hydraulic Conditions

Abstract: Abstract:Reclaimed water is an important supplementary source for fresh water. Purification is necessary prior to utilization in order to minimize the pollution and human-health risk. A three-year experiment was carried out to study the removal of nitrogen and organics through a simulated soil aquifer treatment (SAT) system under continuous wetting and wetting/drying conditions. The removal performance of nitrogen and chemical oxygen demand (COD) was improved in the wetting/drying column. The average removal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…All three processes are microbially mediated and may occur concurrently (Long et al, 2013). Denitrification is favored under suboxic to anoxic conditions and requires abundant electron donors (often organic carbon); these conditions may exist in shallow soils during infiltration for MAR (Wang et al, 2018) and related management strategies aquifer storage and recovery (ASR) and soil aquifer treatment (SAT) (Mienis and Arye, 2018;Pan et al, 2017;Vanderzalm et al, 2013Vanderzalm et al, , 2018. Temperature, pH, saturation, vegetation, and other factors have also been shown to influence denitrification rates (Hiscock et al, 1991;Rao and Malini, 2014;Xiong et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…All three processes are microbially mediated and may occur concurrently (Long et al, 2013). Denitrification is favored under suboxic to anoxic conditions and requires abundant electron donors (often organic carbon); these conditions may exist in shallow soils during infiltration for MAR (Wang et al, 2018) and related management strategies aquifer storage and recovery (ASR) and soil aquifer treatment (SAT) (Mienis and Arye, 2018;Pan et al, 2017;Vanderzalm et al, 2013Vanderzalm et al, , 2018. Temperature, pH, saturation, vegetation, and other factors have also been shown to influence denitrification rates (Hiscock et al, 1991;Rao and Malini, 2014;Xiong et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…COD was primarily removed via microorganism biodegradation [25]. Different sources of pollution can lead to different microbial community compositions, which may result in large differences in the COD degradation coefficient [26].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the SAT system mainly relies on the adsorption of medium to intercept nitrogen in wastewater and decrease its concentration to the reference discharge standard. The removal efficiency of the SAT system for nitrogen in sewage is impacted by the hydraulic load, medium type, and other factors, and the average rejection rate is between 50 and 75% [23,24]. If a repair mechanism in the SAT system is enhanced, its removal effect on specific pollutants will be improved [25,26].…”
Section: Introductionmentioning
confidence: 99%